Colonialism, development, and the environment : railways and deforestation in British India, 1860-1884 - Das, Pallavi V. (Palgrave Macmillan, 2015)
This study explores the confluence of economy and ecology in British India, showing that Britain initiated economic development strategies in India in order to efficiently extract resources from it. It looks specifically at how state railway construction and forest conservation efforts took on a cyclical, almost symbiotic relationship.